John X. Merriman : the making of a South African statesman (1869-1878) - Gruber, R F J (Rhodes University, Faculty of Humanities, Department of History, 1961)
With the possible exception of Hofmeyr and Schreiner, there is no Cape statesman whose career raises more tantalising questions than that of John X. Merr1man. Last Prime Minister of the Cape Colony, doyen of Parliamentarians, brilliant orator, versatile administrator, veteran politician, his public life stretched across fifty-five years of south African History. He entered upon it before the grant of Responsible Government, the discovery of diamonds and gold, and the awakening. of Afrikaner Nationalism; he departed from it on the eve of the Statute of Westminster, the establishment of Iscor and the coming to power of Hertzog and Malan. His contemporaries looked upon him as a man of immense knowledge and olympian ability. In the eyes of many his position as leader of the largest and oldest settled community in South Africa, not to mention his role as heir to the Cape tradition, made him the natural choice as first Prime Minister of the Union he had helped to establish. He was not called to office. Barely seventy, in the full maturity of his years, he withdrew trom active political leadership in the country of his adoption. He is hardly remembered today. This thesis seeks to contribute something to an understanding of the man and an assessment of his qualities by a study of his formative years. It attempts both to reconstruct his personality and analyse the nature of his statesmanship - not only by an examination of the role he played in the years under review, but also by an assessment of the part he failed to play. For this purpose both the structure of Cape politics and the ramifications of the various problems that presented themselves have been explored in greater detail than might otherwise have been the case.
Keywords: Merriman, John Xavier, 1841-1926; Statesmen -- South Africa -- Biography; South Africa -- Politics and government -- 1836-1909